PENGARUH VARIASI BESAR SUDUT KAMPUH V TUNGGAL TERHADAP STRUKTUR MIKRO, KEKERASAN, DAN KEKUATAN TARIK MATERIAL BAJA SS400 DENGAN METODE PENGELASAN SMAW - muhammad farid anshori; Suharno Suharno; Yuyun Estriyanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
The aim of this research is to determine the effect of the groove angle to the microstructure, hardness, and tensile strength on SS400 steel alloys before (raw material) and after welding using the Shielded Metal Arc Welding (SMAW) method.This research used experimental method with descriptive comparative data analysis. The tool used for microstructure test is Olympus Metallurgical Microscope, using Vickers Hardness Tester for hardness test, and using the Universal Testing Machine for tensile test.Based on the data, it could be concluded that the results of the microstructure test showed an increase in pearlite structure after welding. In raw material, ferrite structures are seen evenly but on welding, results using the SMAW method with a 50⁰, 60⁰, and 70⁰ weld groove angles indicated that ferrite is reduced in each specimen, so the pearlite structure is very dominating. The number of hardness and tensile strength on the welding results indicate a difference in the level of hardness and tensile strength. Specimens with a 70o groove angle have a higher hardness level of 276 VHN when compared to 50⁰ groove angle specimens of 248 VHN and 60o of 255 VHN. Specimens with a 70⁰ groove angle have a higher tensile strength which is 432.51 MPa when compared to the 50o groove angle specimens of 407.56 MPa and 60⁰ at 425.69 MPa. The tensile strength test results in raw material amounted to 401.94 MPa. This study shows that welding with variations of groove angle changes the microstructure and affects the hardness and tensile strength of SS400 steel alloys.